Exploring ultra-fast charge transfer and vibronic coupling with N 1s RIXS maps of an aromatic molecule coupled to a semiconductor - O'Shea, James N.; Handrup, Karsten; Temperton, Robert H.; Gibson, Andrew J.; Nicolaou, Alessandro; Jaouen, Nicolas (American Institute of Physics, 2017)
We present for the first time two-dimensional resonant inelastic x-ray scattering (RIXS) maps of multilayer and monolayer biisonicotinic acid adsorbed on the rutile TiO2(110) single crystal surface. This enables the elastic channel to be followed over the lowest unoccupied molecular orbitals resonantly excited at the N 1s absorption edge. The data also reveals ultra-fast intramolecular vibronic coupling, particularly during excitation into the LUMO-derived resonance. Both elastic scattering and the vibronic coupling loss features are expected to contain the channel in which the originally excited electron is directly involved in the core-hole decay process. This allows RIXS data for a molecule coupled to a wide bandgap semiconductor to be considered in the same way as the core-hole clock implementation of resonant photoemission spectroscopy (RPES). However, contrary to RPES measurements, we find no evidence for depletion of the participator channel under the conditions of ultra-fast charge transfer from the molecule to the substrate densities of states, on the timescale of the core-hole lifetime. These results suggest that the radiative core-hole decay processes in RIXS are not significantly modified by charge transfer on the femtosecond timescale in this system.